Mott gap collapse in lightly hole-doped Sr2−xKxIrO4 - Nelson, J. N.; Parzyck, C. T.; Faeth, B. D.; Kawasaki, J. K.; Schlom, D. G.; Shen, K. M. (Nature communications, 2020)
The evolution of Sr 2 IrO 4 upon carrier doping has been a subject of intense interest, due to its similarities to the parent cuprates, yet the intrinsic behaviour of Sr 2 IrO 4 upon hole doping remains enigmatic. Here, we synthesize and investigate hole-doped Sr 2− x K x IrO 4 utilizing a combination of reactive oxide molecular-beam epitaxy, substitutional diffusion and in-situ angle-resolved photoemission spectroscopy. Upon hole doping, we observe the formation of a coherent, two-band Fermi surface, consisting of both hole pockets centred at ( π , 0) and electron pockets centred at ( π /2, π /2). In particular, the strong similarities between the Fermi surface topology and quasiparticle band structure of hole- and electron-doped Sr 2 IrO 4 are striking given the different internal structure of doped electrons versus holes. Doped Sr 2 IrO 4 is of interest because of its close similarities to La 2 CuO 4 , a parent compound of the cuprates. Nelson et al. reveal the intrinsic evolution of its electronic structure with hole doping by avoiding the strong in-plane disorder introduced by previously used chemical substitutions.